DETERMINAN KEPEMILIKAN ASING DAN SIZE DALAM MELAKUKAN TRANSFER PRICING - Rifan, Dinda Fali; Ali, Karnila (Universitas Muhammadiyah Metro Lampung, 2023)
The mining sector is a sector that has enormous potential in Indonesia. Mineral sources are taken directly from the earth and require enormous costs so that the ownership of shares in mining companies comes from within and outside the country. Foreign ownership and the size of a mining company are suspected to be the company's motive for carrying out transfer pricing. This study aims to analyse the determinants of foreign ownership and size in transfer pricing. The research method used uses a quantitative approach, with the study population being mining companies listed on the Indonesian Sharia Stock Index (ISSI) for 2016-2020. The samples in this study were 7 mining companies in ISSI with the sample selection using the purposive sampling method. The data samples were tested using descriptive analysis techniques and to test the hypothesis were tested using multiple linear regression analysis. The results in this study indicate that foreign ownership has no effect on transfer pricing decisions, as well as size has no effect on transfer pricing. The result also shows that foreign ownership and size have no effect on transfer pricing. This shows that the company's motive for carrying out transfer pricing does not come from foreign ownership and company size but from other factors. Keywords: foreign ownership, mining, size, transfer pricing, ISSI.